Эколого-фаунистический обзор скакунов рода Cicindela L. (Coleoptera, Carabidae) Украины - Петрусенко, А.А.; Петрусенко, С.В. (Вестник зоологии, 1970)
Род Cicindela L. на Украине представлен 18 видами. В статье прослежено их распространение в географических зонах УССР и распределение в естественных и культурных биотопах. Дана зоогеографическая характеристика видов. Установлены трофические связи некоторых из них и указаны их враги (членистоногие и птицы). Пять видов активны днем и ночью. The genus Cicindela L. is presented in the Ukraine by 18 species. Their distribution
in the geographical zones of the Ukrainian SSR and in the natural and cultural biotopes
was observed. Zoogeographical characteristic of the species is given. Trophic connections
of some of them are established and their enemies are shown (arthropodes and birds).
All the tiger beetles are active in the day-time, and five species — at night as well.